Identification of biological targets of therapeutic intervention for clear cell renal cell carcinoma based on bioinformatics approach - Chen, Yongsheng (Cancer Cell Int, 2016)
BACKGROUND: We aimed to discover the potential microRNA (miRNA) targets and to explore the underlying molecular mechanisms of clear cell renal cell carcinoma (ccRCC). METHODS: Microarray data of GSE16441 was downloaded from Gene Expression Omnibus database. Differentially expressed genes (DEGs) and differentially expressed miRNAs between ccRCC tumors and matched non-tumor samples were analyzed. Target genes of differentially expressed miRNAs were screened. Besides, functional enrichment analysis of DEGs was performed, followed by protein–protein interaction (PPI) network construction and sub-module analysis. Finally, the integrated miRNA-DEGs network was constructed. RESULTS: A total of 1758 up- and 2465 down-regulated DEGs were identified. Moreover, 15 up- and 12 down-regulated differentially expressed miRNAs were screened. The up-regulated DEGs were significantly enriched in pathways such as cell adhesion molecules and focal adhesion. Besides, the down-regulated DEGs were enriched in oxidative phosphorylation, and citrate cycle (TCA cycle). Moreover, eight sub-modules of PPI network were obtained. Totally, eight down-regulated miRNAs were identified to significantly regulate the DEGs and miRNA-200c that could regulate collagen, type V, alpha 2 (COL5A2) as well as COL5A3 was found to be the most significant. Additionally, 10 up-regulated miRNAs were identified to be significantly associated with the DEGs. Thereinto, miRNA-15a that could regulate ATPase, H(+) transporting, lysosomal 21 kDa, V0 subunit b (ATP6V0B) and miRNA-155 were found to be the most significant. CONCLUSIONS: miRNA-200c that could regulate COL5A2 and COL5A3, miRNA-15a that could regulate ATP6V0B and miRNA-155 may play key roles in ccRCC progression. These miRNAs may be potential targets for ccRCC treatment.